Associations of oral fluid MMP‐8 with periodontitis in Swiss adult subjects. (11th October 2017) - Mauramo, M; Ramseier, AM; Mauramo, E; Buser, A; Tervahartiala, T; Sorsa, T; Waltimo, T
Abstract : Objective: MMP‐8 is a prominent collagenase in periodontal disease. This cross‐sectional study examined whether MMP‐8 levels in saliva and gingival crevicular fluid (GCF) are associated with periodontitis in a Swiss population. Subjects and Methods: A total of 258 subjects (107 m, 151 f, mean age: 43.5 yr; range: 21–58 yr) acquired from the Swiss bone marrow donor registry participated in the study. Saliva and GCF samples were collected from subjects followed by a thorough dental and periodontal examination. MMP‐8 levels were determined with immunofluorometric assay. Associations of MMP‐8 levels with periodontal diagnosis, probing pocket depth (PPD) and bleeding on probing were statistically analysed with Pearson chi‐square test, Spearman's rho and logistic regression analysis. Results: MMP‐8 in GCF correlated with MMP‐8 in saliva ( p < .001). Periodontitis was more common ( p < .001) among subjects with high levels of MMP‐8 in saliva and/or GCF compared with subjects with low levels of MMP‐8. Higher MMP‐8 levels in GCF and saliva were associated with any periodontal diagnosis (mild, moderate or severe), greater PPD, and bleeding on probing ( p < .05). When age, gender, smoking, body mass index, number of medications and decayed, missing and filled teeth were adjusted for, all observed associations remained statistically significant. The area under curve of receiver‐operating characteristic was 0.67 for saliva and 0.71 for GCF. Conclusion: Elevated MMP‐8 levels both in saliva and GCF are associated with periodontitis in a normal adult population.